Association between Vitamin D and Calcium Level and BMD Alteration in Post-Menopausal Osteoporosis Patients Treated with Bisphosphonate Therapy for at Least 1 Year in Saiful Anwar Hospital Malang - Hamzah, Hamzah; Huwae, Thomas Erwin Christian Junus; Chodidjah, Chodidjah (Indonesian Society for Cancer Chemoprevention, 2021)
Post-menopausal osteoporosis is a degenerative disease among post-menopausal women. In Indonesia, women over 50 years old get post-menopausal osteoporosis.The therapy should be comprehensive and continous. Bisphosphonate therapy is one of the most preferable therapeutic option for maintaining bone density. Calcium and vitamin D have a role in increasing osteoblastic activity. The objective of this study was to describe the vitamin D and calcium in bone mineral density (BMD) of hip and spine in postmenopausal woman with biphosphonat therapy. This study is a cross-sectional, observational analytic. The subject were female patients with post-menopausal osteoporosis treated in clinic of RSUD dr. Saiful Anwar Malang, who had received routine bisphosphonate for at least 1 year. The method was collecting the patient data, who received oral and injectie bisphosphonate therapy, serial BMD test,hip and spine, vitamin D and calcium level in serum test. Total sample 25 participan, the association between BMD change (Δ BMD), vitamin D and calcium level, were analyzed.with Chi Square test then continued using Spearman correlation test. Vitamin D levels in Δ BMD Spine in participants was less <30 ng/ml, mean 16.8+6.95 14 respondents (56%), and 6 respondens (24%) 10.05+5.28, normal vitamin D levels were 5 respondents (20%) mean 34.16+5.10. Vitamin D levels in Δ BMD Hip in participants was less <30 ng/ml, mean 15.19+7.7 12 respondents (48%), and 8 respondens (32%) 12.30+5.57, normal vitamin D levels were 5 respondents (20%) 33.66+5.40. Calcium levels in BMD spine 9.60+0.45, 14 respondents (56%), and 11 respondens (44%) 9.59+0.52. There is a significant and moderate relationship between vitamin D levels with Δ BMD spine (p=0.009, r=0.564) and Hip (p=0.039, r= 0.480) T Blood calcium levels with Δ BMD changes unrelated (normal). There is a significant association between vitamin D levels spine and Hip Δ BMD. Blood calcium levels with Δ BMD changes unrelated.Keywords: Osteoporosis, Bisphosphonate, Vitamin D levels, Calcium levels.